2021
DOI: 10.3390/ph14080828
|View full text |Cite
|
Sign up to set email alerts
|

New Sulfanilamide Derivatives Incorporating Heterocyclic Carboxamide Moieties as Carbonic Anhydrase Inhibitors

Abstract: Carbonic Anhydrases (CAs) are ubiquitous metalloenzymes involved in several disease conditions. There are 15 human CA (hCA) isoforms and their high homology represents a challenge for the discovery of potential drugs devoid of off-target side effects. For this reason, many synthetic and pharmacologic research efforts are underway to achieve the full pharmacological potential of CA modulators of activity. We report here a novel series of sulfanilamide derivatives containing heterocyclic carboxamide moieties whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 67 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…The aim of this study is to support and extend our previous studies [51][52][53] on hCA as a target against diverse pathological conditions. Thus, herein we report the synthesis of two different groups of compounds, one of which is pyrazolo [4,3-c]pyridine sulfonamides (1a-f) and the other sulfonamide derivatives of different hetrocyclic moieties (1g-1k), and the evaluation of their inhibitory activities towards four human CAs (I, II, IX, and XII) as well as 3β and 3γ CAs from different bacterial strains.…”
Section: Introductionmentioning
confidence: 53%
“…The aim of this study is to support and extend our previous studies [51][52][53] on hCA as a target against diverse pathological conditions. Thus, herein we report the synthesis of two different groups of compounds, one of which is pyrazolo [4,3-c]pyridine sulfonamides (1a-f) and the other sulfonamide derivatives of different hetrocyclic moieties (1g-1k), and the evaluation of their inhibitory activities towards four human CAs (I, II, IX, and XII) as well as 3β and 3γ CAs from different bacterial strains.…”
Section: Introductionmentioning
confidence: 53%
“…Second, compounds 103(a-o) were reacted with propargyl bromide to produce compounds N-alkyl-3-prop-2-yn-1-ylthio)-5H- [1,2,4]triazino [5,6b] indole derivatives 104(a-o) followed by the reaction with Newly synthesized compounds 105(a-o) were screened for inhibitory activity against human (h) isoforms of CA, hCA I, II, XIII (cytosolic isoforms), and hCA IX (tumor related isoform) by the stopped-flow CO 2 hydrase assay method by taking AAZ as standard drug and it was observed that 105i (X = F, R = -CH (CH 3 ) 2 ) was found to show potent activity against hCA II and hCA XIII with K i values of 7.7 and 34.9 nM, respectively, as compared to AAZ (K i = 12.1 nM) due to the presence of fluoro-group at fifth position of indole moiety and isopropyl group attached to nitrogen of indole ring [34] (Scheme 15). (110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126)(127)(128)(129).…”
Section: S C H E M E Synthesis Of 94(a-s)mentioning
confidence: 99%
“…The m structure of these compounds is shown in Figure 4. The derivatives 1-24 and A are either simple aromatic or heterocyclic sulfonamides, and are frequently building blocks to create novel potent and selective pharmaceuticals [43,44]. T AAZ-EPA (see Table 1 for their identification) involves classical CA inhibitors (CA in clinics for managing and treating glaucoma, idiopathic intracranial hype altitude sickness, congestive heart failure, epilepsy, and other diseases [4,[36][37][38]4 Among nonantibiotic sulfonamides, primary sulfonamides (R'-SO 2 -NH 2 ) showed the most promising results due to their Zn(II) ion-binding properties; thus, they have received increased attention due to their capability to specifically inhibit CAs [42].…”
Section: Inhibition Profile Of Mpaca With Sulfonamidesmentioning
confidence: 99%
“…The molecular structure of these compounds is shown in Figure 4. The derivatives 1-24 and AAZ-EPA are either simple aromatic or heterocyclic sulfonamides, and are frequently used as building blocks to create novel potent and selective pharmaceuticals [43,44]. The series AAZ-EPA (see Table 1 for their identification) involves classical CA inhibitors (CAIs) used in clinics for managing and treating glaucoma, idiopathic intracranial hypertension, altitude sickness, congestive heart failure, epilepsy, and other diseases [4,[36][37][38]43,45].…”
Section: Inhibition Profile Of Mpaca With Sulfonamidesmentioning
confidence: 99%